Strategi Pembelajaran Dengan Contextual Teaching And Learning (Ctl) Pada Pelajaran Menggambar Konstruksi Di Sekolah Menegah Kejuruan (Smk) - Sitorus, Michael; fitria, Fitria (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2019)
Facilities for students' activities in actively developing their competencies are very difficult to find and implement their ideas, and moreover to be aware in applying their strategies, so students do not have the life skills as independent people. This type of research is actions that occur in class using the Contextual Teaching and Learning (CTL) method. The purpose of this study is to explore the benefits of the Contextual Teaching and Learning (CTL) method in improving learning outcomes in drawing construction in SMK. Data collection techniques carried out through interviews, documentation, and observation methods. Analysis of the data to be used in this research is descriptive percentages. The results of the study concluded that the learning strategy with the Contextual Teaching and Learning (CTL) method can improve student learning outcomes. Based on the results of the first cycle-assessment on the initial ability task with an average value of 33.15 and the first cycle assignment with an average of 40.21 then an increase in the second cycle with an average of 80.36. The Contextual Teaching and Learning (CTL) method can be used as an alternative method of learning in class so that learning activities can run more effectively in construction drawing lessons and can improve student learning outcomes.